Development of Babinsa 0205/TK Performance Monitoring System using Copras Complex Proportional Assessment Method - Sundari, Razdnie Rhaka; Amrullah, Amrullah (Ilmu Bersama Center, 2025)
This study aims to develop a performance monitoring system for Babinsa 0205/TK utilizing the COPRAS (Complex Proportional Assessment) method. COPRAS, a Multi-Criteria Decision Analysis (MCDA) technique, allows for the evaluation of performance based on various criteria such as discipline, initiative, and communication skills. The system is designed to provide an objective and proportional assessment of Babinsa performance by assigning weights to each criterion and calculating the overall score. The development of this system has demonstrated improved accuracy in performance evaluation and enhanced transparency, providing a solid foundation for decision-making in performance management. The implementation of this system is expected to enhance the effectiveness of monitoring, accountability, and performance improvement for Babinsa, thereby supporting better execution of duties at the village level.